A simple and effective predictor to design novel fluorite-structured High Entropy Oxides (HEOs). (1st January 2021) - Spiridigliozzi, Luca; Ferone, Claudio; Cioffi, Raffaele; Dell'Agli, Gianfranco
Abstract: High-Entropy Oxides (HEOs) are a totally new class of ceramic materials that have recently attracted many scientific attentions. However, the huge intrinsic complexity and the massive number of possible combinations characterizing such systems make it hard to predict a priori their properties and their crystal structures. Moreover, the idea of designing and engineering new materials by using entropy as a driving force is conceptually exciting and intellectually stimulating. Thus, we acknowledged that predicting and synthesizing unknown entropy-stabilized single-phases of a given formula in a given crystal structure could be of great interest to the HEOs research community and, through a systematic study of 18 samples of equimolar 5-component Rare Earths-based oxides, we were able to elaborate a simple and effective predictive model to design HEOs stabilized in a single-phase fluorite-like structure. The novelty of our model, other than its simplicity and immediacy, consists in pointing out that the "dispersion" of the cationic radii of the involved elements of a certain system (expressed in terms of their standard deviation) is crucial for stabilizing fluorite-structured HEOs. Definitely, for systems owning standard deviations of the involved elements cationic radii (coordination VIII) distribution higher than 0.095, single-phase fluorite-structured systems are formed; otherwise, for s < 0.095 firstly biphasic (fluorite and bixbyite) systems are formed and then single-phase bixbyite-structured systems are formed. Graphical abstract: Image, graphical abstract